2004
DOI: 10.2136/vzj2004.0775
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Reactive Transport Modeling of Seasonal Infiltration Events and Stable Isotope Fractionation in Unsaturated Zone Pore Water and Vapor at the Hanford Site

Abstract: Numerical simulations of transport and isotope fractionation provide a method to quantitatively interpret vadose zone pore water stable isotope depth profiles based on soil properties, climatic conditions, and infiltration. We incorporate the temperature‐dependent equilibration of stable isotopic species between water and water vapor, and their differing diffusive transport properties into the thermodynamic database of the reactive transport code TOUGHREACT. These simulations are used to illustrate the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Using data from 25 sites across the world, Sprenger, Leistert, Gimbel, and Weiler () revealed that the evaporative fractionation effects were generally limited to the upper 30 cm of the soil, but that effect was climate dependent. Deep progression fronts up to 2–3 m have been reported for sites in arid climates (e.g., Beyer et al, ; Singleton, Sonnenthal, Conrad, DePaolo, & Gee, ), whereas in tropical climates, a clear vertical gradient in the soil water isotopic signal is usually only observed under pronounced dry seasons (Querejeta, Estrada‐Medina, Allen, & Jiménez‐Osornio, ). In tropical regions, the high humidity (Goller et al, ; Good, Noone, & Bowen, ) and typically dense vegetation cover (Dubbert, Cuntz, Piayda, Maguás, & Werner, ) can both contribute to relatively low soil evaporation.…”
Section: Discussionmentioning
confidence: 85%
“…Using data from 25 sites across the world, Sprenger, Leistert, Gimbel, and Weiler () revealed that the evaporative fractionation effects were generally limited to the upper 30 cm of the soil, but that effect was climate dependent. Deep progression fronts up to 2–3 m have been reported for sites in arid climates (e.g., Beyer et al, ; Singleton, Sonnenthal, Conrad, DePaolo, & Gee, ), whereas in tropical climates, a clear vertical gradient in the soil water isotopic signal is usually only observed under pronounced dry seasons (Querejeta, Estrada‐Medina, Allen, & Jiménez‐Osornio, ). In tropical regions, the high humidity (Goller et al, ; Good, Noone, & Bowen, ) and typically dense vegetation cover (Dubbert, Cuntz, Piayda, Maguás, & Werner, ) can both contribute to relatively low soil evaporation.…”
Section: Discussionmentioning
confidence: 85%
“…Earlier work of Singleton et al . () used a multiphase reactive transport model (TOUGH‐REACT) and found that the magnitude of the isotopic composition shifts to more depleted values in deep pore waters of the unsaturated zone and is inversely related with the rate of deep infiltration. They were able to illustrate the evolution of the stable isotope profile alternating between wet and dry seasons.…”
Section: Interpretation and Modeling Of Evaporation Profiles In The Umentioning
confidence: 99%
“…[]). Several pore water isotope studies showed that the kinetic fractionation is usually limited to the upper −0.2 to −0.3 m in temperate regions [e.g., Komor and Emerson , ; Gazis and Feng , ; Zhang et al ., ; Sutanto et al ., ], increases to 0.5 m in Mediterranean climates [ Simonin et al ., ; Oshun et al ., ], and can reach down to −3 m in arid climates [ Allison and Hughes , ; Singleton et al ., ]. Figure supports these findings, where we present the lc‐excess over the depth.…”
Section: Atmospheric Influencesmentioning
confidence: 99%